Analisis Pelaksanaan Pengawasan Pembangunan Jalan Akses Menuju Kebun Raya Sriwijaya Kabupaten Muara Enim - Siti Zubaidah (Jurnal Pemerintahan dan Politik, 2019)
AbstractThe road construction is a vital requirement as a major supporter of the dynamics and economic activity, both at central and local and regional development as well as major infrastructures for the national economy. As an important part in the activities of the road management Roads Towards Botanical Sriwijaya Muara Enim regency were in need of supervisory activities road handed over to a third party or agent . The results of the study are limited capability of human resources supervisor professional while goal setting tailored to the type of work while still limited budget available for operational purposes supervisor. For the problem of the execution time is already in accordance with the applicable procedures and agreed upon by several stakeholders, sometimes constrained by natural conditions, especially when the rainy season is very annoying time of the existing activities in the field. Scheduling is the process of preparing a list of work to be done to achieve and realize a certain goal and Examination Report has been carried out in accordance with the Terms of Reference but there are obstacles reports submitted did not follow up on the implementation of the work.Keywords: Analysis, Implementation, Monitoring, Development, Road AccessAbstrakPembangunan jalan merupakan kebutuhan yang sangat vital sebagai pendukung utama dinamika dan aktivitas ekonomi, baik di pusat maupun daerah dan pengembangan wilayah serta sebagai prasarana penunjang yang utama bagi perekonomian nasional. Sebagai bagian penting dalam kegiatan penyelenggaraan jalan maka Pembangunan Jalan Akses Menuju Kebun Raya Sriwijaya Kabupaten Muara Enim juga memerlukan adanya kegiatan pengawasan jalan yang diserahkan kepada pihak ketiga atau konsultan. Terbatasnya kemampuan sumber daya manusia pengawas yang profesional sedangkan penentuan tujuan disesuaikan dengan jenis pekerjaan sedangkan anggaran yang tersedia masih terbatas untuk keperluan operasional pengawas. Untuk masalah waktu pelaksanaan memang sudah sesuai dengan prosedur yang berlaku dan disepakati oleh beberapa pihak terkait, terkadang terkendala oleh keadaan alam terutama waktu musim penghujan sangat mengganggu waktu pelaksanaan kegiatan yang ada dilapangan. Penjadwalan merupakan proses penyusunan daftar pekerjaan yang akan dilakukan untuk mencapai dan mewujudkan suatu tujuan tertentu dan Laporan Hasil Pemeriksaan sudah dilakukan sesuai dengan Kerangka Acuan Kerja namun laporan yang disampaikan terdapat kendala tidak adanya tindak lanjut dari pelaksanaan pekerjaan.Kata kunci : Analisis, Pelaksanaan, Pengawasan, Pembangunan, Jalan Akses